Uncovering the natural variability of araucariacean exudates from ex situ and in situ tree populations in New Caledonia using FTIR spectroscopy - Seyfullah,Leyla J.; Roberts,Emily A.; Jardine,Phillip E.; Rikkinen,Jouko; Schmidt,Alexander R. (PeerJ Analytical Chemistry, 2022)
Background Understanding the natural variability of plant resins is crucial for evaluating the chemical information stored in ambers that may support inferring palaeoenvironmental conditions. However, even among extant resin-producing plants, the variation of resinous exudates within and between tree genera and species is still poorly understood. Methods We analysed plant exudates from across the Araucariaceae in New Caledonia using Fourier-transform infrared spectroscopy in attenuated total reflection mode (FTIR-ATR). Both, wild (in situ) and arboretum grown (ex situ) populations were used to uncover the effects of intergeneric, inter- and intraspecific variation of the araucariacean plants on the resin chemistry. Results We show that even resins from the same species in the same habitat do have natural (intraspecific) chemical variation. Some of the variation can result from the degree of resin polymerisation, but this is not the only source of variation. Wild sourced resins have greater natural intraspecific chemical variation than the arboretum sourced ones. Interspecific and intergeneric differences were not easy to distinguish in the resins sampled. This has strong implications for the evaluation of the chemical information from worldwide ambers: multiple samples should be analysed to give a more accurate picture of the natural chemical variation present and how this may or may not overlap with the chemistries of other resin types. Additionally we discovered that the Araucariacean species can produce up to three distinct types of exudate (gum, resin, and gum resin). This is the first time that gum resins have been identified and characterized with FTIR-ATR. We also provide a guide on how to distinguish the exudate types when using FTIR-ATR.
Keywords: Agathis; Amber; Araucariaceae; Araucaria; Gum; Gum resin; Resin; New Caledonia; FTIR-ATR